The Role of Family in Managing Financial Stress and Economic Hardship - Asadi, Kobra; Yousefi, Zahra; Parsakia, Kamdin (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: This study aims to explore the role of family dynamics in managing financial stress and economic hardship. By examining how families navigate these challenges through various strategies and coping mechanisms, the research seeks to provide a deeper understanding of the impact of economic hardship on family relationships and individual well-being.Methods: A qualitative research design was employed, utilizing semi-structured interviews to collect data from 20 participants. Participants were selected through purposive sampling to ensure diverse perspectives. Data were analyzed using NVivo software, with thematic analysis guiding the identification and categorization of key themes. Theoretical saturation was reached, ensuring comprehensive coverage of the participants' experiences.Results: The study identified three main themes: family roles and responsibilities, coping strategies for financial stress, and the impact on family dynamics. Families adopted joint decision-making, budget creation, and income pooling to manage finances. Emotional and practical support were vital coping mechanisms, with open communication and resource sharing being prominent strategies. Economic hardship led to changes in family relationships and significant impacts on mental health, particularly for parents and children.Conclusion: Family dynamics play a critical role in managing financial stress and economic hardship. Effective financial management, open communication, and supportive relationships are essential for mitigating the adverse effects of economic pressure. The findings underscore the need for targeted interventions and support systems to help families navigate economic challenges and maintain their well-being.